Analisis Pengaruh Kualitas Pelayanan & Harga Terhadap Kepuasan Konsumen Restoran Nasi Kebuli Kemonya - Ramadhani, Aisyah Fatihah; Kasih, Yulizar (Universitas Multi Data Palembang, 2024)
This research aims to examine service quality and price on consumer satisfaction. The population in this study were consumers who had visited Nasi Kebuli Kemonya more than twice. With 340 samples and using the Slovin technique. Data analysis uses multiple linear regression analysis. The results of the analysis show that service quality and price have a positive and significant effect partially and simultaneously.